Green entrepreneurship in the era of sustainability: the relationship between intent, institutional support, and student behavior - Mukhammad Kholid Mawardi; Arif Yustian Maulana Noor; Lintang Edityastono; Siti Nur ‘Atikah Zulkiffli; Faizah Mashahadi (Cogent Business & Management)
Green entrepreneurial intentions have garnered substantial attention in higher education, yet the transformation of these intentions into tangible behaviors remains underexplored, particularly in diverse cultural settings. This study addresses this gap by examining the roles of university and governmental support in enabling green entrepreneurial behavior among students in Indonesia and Malaysia, offering a novel cross-cultural perspective. The study surveyed 111 respondents from Indonesia and Malaysia, focusing on students interested in green entrepreneurship. The analysis employed Structural Equation Modeling (SEM) to investigate the relationships among latent variables, including green entrepreneurial intentions, green entrepreneurial behavior, environmental institutional support, and university environmental support. Findings indicate that while green entrepreneurial intentions significantly influence behavior, university support alone is insufficient to drive green entrepreneurship, emphasizing the need for practical experiences alongside institutional backing. The results highlight the critical role of government policies in promoting green entrepreneurship among students, demonstrating that supportive regulatory frameworks and incentives can effectively encourage sustainable business practices. These insights contribute to developing more effective policies and programs aimed at fostering green entrepreneurship, thereby supporting both environmental and economic sustainability at local and global levels.